Economic Growth, Financial Development, Energy Consumption and Life Expectancy: Fresh Evidence from ASEAN countries - Hendrawaty, Ernie; Shaari, Mohd Shahidan; Kesumah, Fajrin Satria Dwi; Ridzuan, Abdul Rahim (International Journal of Energy Economics and Policy, 2022)
The study examines the relationship between economic growth and life expectancy by considering the potential role of financial development and energy consumption in ASEAN Countries. Unit root testing was applied to check the level stationarity data before checking for cointegration between variables using the Error Correction Term (ECT) approach, and ARDL bounds testing was applied for cointegration with structural damage that occurred at a specific time using the Pooled Mean Group (PMG) and Pooled Mean Group (MG). The empirical results showed the existence of cointegration among variables. PMG was selected based on Hausmann Test that indicated energy consumption could significantly and positively affect life expectancy. Therefore, ASEAN countries would be extensively dependent on non-renewable energy to generate their economic activities in the long run. In contrast, in the short run, higher economic growth can reduce life expectancy in most developing countries, as energy consumption is examined to affect life.